2014
DOI: 10.1136/bmjopen-2014-006554
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of associations between environmental exposures and development of asthma in children aged up to 9 years

Abstract: Objectives: Childhood asthma is a complex condition where many environmental factors are implicated in causation. The aim of this study was to complete a systematic review of the literature describing associations between environmental exposures and the development of asthma in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 150 publications
2
119
1
3
Order By: Relevance
“…Contradictory data are found in the literature, probably due to the fact that PM 2.5 levels are linked to other pollutants through a cocktail effect [11]. In addition, exposure to PM 2.5 was here evaluated at day 0 and in the previous week at five sites; however, such exposure has been found to be a risk factor for asthma-related ED visits up to 5 days before the medical consultation [12,14,17,29].…”
Section: Discussionmentioning
confidence: 78%
“…Contradictory data are found in the literature, probably due to the fact that PM 2.5 levels are linked to other pollutants through a cocktail effect [11]. In addition, exposure to PM 2.5 was here evaluated at day 0 and in the previous week at five sites; however, such exposure has been found to be a risk factor for asthma-related ED visits up to 5 days before the medical consultation [12,14,17,29].…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, studies examining the impact of breastfeeding on the development of asthma have reported conflicting results [35,36], and generating more definitive data with randomised controlled trials is not ethical or feasible.…”
Section: Breastfeedingmentioning
confidence: 94%
“…Masing-masing bulan pemberian ASI eksklusif menurunkan kejadian asma 17% , 12% , 11% , 12% , dan 9% berturut-turut pada umur 2, 3, 4, dan 5 tahun. 22,23 Tidak terdapat perbedaan prevalensi kejadian alergi antara anak yang memiliki skor sedang-tinggi maupun rendah pada penilaian skor deteksi dini alergi. Atopi bersifat diturunkan, risiko seorang anak mengalami alergi yang diperantari IgE sekitar 40%-60% bila kedua orang tua atopi.…”
Section: Pembahasanunclassified